Avaliação micológica ao longo do processamento de salames e influência da umidade relativa sobre a produção de ocratoxina A por Aspergillus westerdijkiae - Parussolo, Gilson (2018)
The salami is a fermented meat product introduced in Brazil by the first Italian immigrants. The organoleptic characteristics of this product are influenced by fungi growing on the sausage surface. If production and maturation is not carried out under hygienic conditions, they can be colonized by toxigenic fungi. The objective of this study was to investigate mycological quality of raw materials, ambient air from the area of production and maturation and surface of salami, as well as to analyze the production and migration of ochratoxin A in salami inoculated with a producer species. Two industries were used for the study, from which samples of raw material (black pepper, nutmeg, wrapper, garlic, spice mix and meat) were obtained for mycological analysis. It was also carried out, in two periods, the sampling of air from the production and maturation areas and the collection of salamis to analyze the fungi present on the surface of the wrapping during maturation. The mycological analyzes were done in 18% Dichloran Glycerol medium (DG18) using surface plating, for analysis of the raw materials and swab smear technique in an area of 25cm2 to evaluate the salami surface. DG18 was also the culture medium used for recovering airborne fungi. For the production of ochratoxin A, Aspergillus westerdijkiae (104 spores) was inoculated on salami surface, which were incubated in different relative humidity (normal maturation, decreasing from 95 to 75% over 35 days; relative humidity of 79%, 85% and 95% for 21 days). Weekly samplings were carried out to verify the presence and distribution of ochratoxin A in the casing, outer border and salami crumb. The raw materials presented low fungal contamination, with the exception of black pepper. For salami, a wide fungal variety was verified in the two industries, predominantly Aspergillus (mainly xerophilic species), Penicillium and Cladosporium. In industry B the presence of Aspergillus westerdijkiae was observed, fungus known as ochratoxin A producer in meat products. The ambient air presented high contamination mainly by Cladosporium sp. followed by Penicillium sp. and Aspergillus sp., being in some cases, above the limit of quantification of the apparatus (>104 CFU / cm3). About half of the species present in the air were also isolated from the salami. A. westerdijkiae has also been identified in industry B. A. westerdijkiae has not been isolated from raw materials. In the case of A. westerdijkiae, ambient air can be considered a critical point in terms of contamination and propagation of fungi in processing areas of food. In salami inoculated with A. westerdijkiae it was not possible to detect ochratoxin A in the first 7 days in both normal maturation and fixed relative humidities. The highest amount of toxin was detected in the casings, with the maximum amount detected at day 14 at the relative humidity of 79% (1135 μg/kg). Under normal maturation the maximum was detected at 21 days (676.5 μg/kg). The toxin was able to migrate from casing into the outer border (87.4 μg / kg at 0.79, 1.55 μg/kg at normal maturation). No migration of the toxin into the salamis core was observed. In conclusion, the presence of toxigenic fungi in salami surface is of public health concern due to their ability to produce mycotoxins as it develops in the casing with diffusion of toxin into the product.